Employability en individuele ontwikkeling op het werk (Employability and individual development at the workplace) - van Dam, K.; van der Heijden, B.I.J.M.; Schyns, B. (Gedrag & Organisatie, 2006)
In the past decades, employability and employee development have received increased attention. Changes within and around organizations have emphasized the need for flexible firms and a multi-skilled work force, while, at the same time, employees have become responsible for their own careers and work security. The present article first reviews recent changes underlying the need for employability and employee development. Subsequently, attention is paid to the concepts of employability and workplace learning, factors affecting learning at work, and age-related influences. With this article, we aim to kick off a new series for Gedrag & Organisatie on employee development and employability in organizations.
EPrint Processing Status: DRO Team waiting for permission from publisher to deposit full text
Keywords: Employee development; Employability; Workplace learning; HRD.